O discurso acadêmico-científico produzido por surdos: entre o fazer acadêmico e o fazer militante - Maria Clara Maciel de Araujo Ribeiro (2012)
We are currently witnessing the entry of the Deaf in post graduated-programs conducting research that in the frontier between the academy and the Deaf Movement. Those are research work that while legitimizing its place in the academy, also attest to his character clearly activist in favor of deaf people. From this discourse, discursive strategies are emanated oriented at controlling the tension established between the researcher subject and the militant subject. It is in this context that this research aims to unravel, in the academic research undertaken by deaf, polyphonic arrangements established between the voice of the deaf researcher and activist voice of the deaf subject, comprising the arrangements and overlays of these voices and images in the thread of the discourse. To this end, three doctoral theses in Educational Studies, produced by Deaf, on topics related to deaf people, were analyzed using French-oriented Discourse Analysis, with the contribution of the Sociology of Scientific knowledge. Specifically, the research was based on the theoretical apparatus of authors like Dominique Maingueneau (2005, 2006, 2008) and Boaventura de Sousa Santos (2005, 2007, 2009). The first, place we before in front of the theories of the French-oriented Discourse Analysis, while the second presents a model of scientific rationality politically oriented. The results indicate that the research analyzed acknowledges their activist part where an I or a We discloses a deaf politically compromised with his people; that the academics and activists actions are understood as mutually conditioning. In general, there is a predominance of the research subject striving to keep the militant subject under control. As an amalgam, these tasks will establish a relationship in the discursive production so as to become, in many occasions, inseparable.